NEEDS ANALYSIS AS THE CORNERSTONE OF THE DESIGN AND DEVELOPMENT OF ONLINE LANGUAGE LEARNING - Ummu Rofikah; Buhanuddin Arafah; Andi Kaharuddin (Universitas Hasanuddin, 2022)
Given the myriads of possible configurations within online learning, careful design and selection of technology and media that count the students' needs and conditions should be at the central attention of the developers in order to accommodate the students' needs and to avoid developing ineffective and unproductive online learning. This study aims at analyzing the needs of the students in the online English language learning at the Intensive Foreign Language Learning Program, Alauddin State Islamic University, Makassar. This study used developmental research. Purposively sampled, 70 respondents participated in this study including 50 students, 10 lecturers, and 10 graduates. Two types of information were analyzed namely the students’ language learning needs and the students’ perceptions of technology and media for their online learning. The findings can be the basis for developing sound online language learning in the program, considering the absence of any research-based online learning there.